Religiosity and Attitudes: A Study of Indonesian Islamic Primary School Students - Ismanto, Hadi; Murtadho, Nurul; Setyosari, Punaji; Wiyono, Bambang Budi (AL-ISHLAH: Jurnal Pendidikan, 2024)
The integration of religious learning significantly shapes students' educational experiences and character development. This study explores specific dimensions of religiosity in the attitudes of Islamic primary school students in Indonesia, focusing on awareness, initiative, and altruism. Using a qualitative design with a grounded theory approach, the research was conducted in 64 classes from grades 1 to 6, involving 1,920 students. Instruments included a guidebook of students' daily worship activities and teacher observations. Data were analyzed using NVivo 14 and Crosstab analysis. The findings reveal that students' external religiosity, influenced by their environment and personal motivation, leads to internal religiosity characterized by conscientiousness, initiative, and altruism. Conscientiousness reflects adherence to religious norms, initiative is shown through disciplined and pious actions, and altruism manifests in helping others based on religious teachings. The study concludes that the development of students' religiosity dimensions results from disciplined and continuous training supported by teachers and parents. The findings highlight the importance of ongoing attention and guidance in fostering altruistic attitudes. These insights have implications for educators, policymakers, and parents, emphasizing the need for comprehensive religious education that promotes ethical behavior and social responsibility. Future research should explore the long-term effects of religious education on moral and social development, its impact across diverse backgrounds, and the role of digital platforms in enhancing religious education.